Third Lithuanian Statute: Origin of its Transcript, Features of the Source and its Impact on Livonia and Courland - Glazauskaitė, Simona (Lietuvos istorijos studijos, 2025)
A German translation of the Third Lithuanian Statute (TLS) is preserved in a manuscript form in the Latvian State Historical Archive (LVVA), within the collections of the Courland Society of Literature and Art and the Courland Province Museum (F. 5759). To date, this source has received almost no scholarly attention. In view of the existing research gap, this article examines the main codicological and textological features of the source, as well as the circumstances of its origin and its adaptation in the Courland Statute and the Livonian Code.The study has revealed that the appearance of the manuscript in the archive of the Society and the Museum in the 19th–20th centuries, and its subsequent transfer to the LVVA, reflects a broader process of collecting historical sources from Courland and Livonia. The acquisition of the manuscript book is associated with antiquarian collecting rather than with practical legal use. A different picture emerges in the context of the 16th–18th centuries, when the German-language version of the TLS was used in Livonian judicial practice and law-making, while the Courland Statute incorporated norms from the TLS.
Keywords: Third Lithuanian Statute; Duchy of Courland; Livonia; Statute of Courland; German language